Creating New Paths? Offshore Wind, Policy Activism, and Peripheral Region Development. (3rd October 2013) - Dawley, Stuart
Abstract This article extends economic geography research on path creation by developing a conceptual framework that moves beyond existing firm‐centric accounts and connects to a wider array of actors and multiscalar institutional contexts that mediate the emergence and development of growth paths. As part of a broader understanding of social and institutional agency, the approach specifically redresses the apparent neglect of the multiple roles of the state and public policy interventions in research on path creation. The framework is used to interpret more than 30 years of path‐creation activities that have placed the peripheral region of North East England at the forefront of the United Kingdom's burgeoning offshore wind sector. The empirical findings reveal how a variety of path‐creation mechanisms have served to shape, and be shaped by, successive causal episodes of complex and geographically situated social agency. Emerging from an episode of entrepreneurial activity, the path's creation was subsequently catalyzed by a decade of strategic and contextual regional policy intervention before a radical restructuring of economic development governance in the United Kingdom created a policy vacuum for the path's development. The analysis of the policy‐on, policy‐off episodes illustrates the potential agency of evolutionary inspired policy interventions in supporting mechanisms of path creation and reveals a varied set of implications for the cohesion and embeddedness of the path's development.